2005
DOI: 10.5194/angeo-23-885-2005
|View full text |Cite
|
Sign up to set email alerts
|

A multi-spacecraft survey of magnetic field line draping in the dayside magnetosheath

Abstract: Abstract. When the interplanetary magnetic field (IMF) encounters the Earth's magnetosphere, it is compressed and distorted. This distortion is known as draping, and plays an important role in the interaction between the IMF and the geomagnetic field. This paper considers a particular aspect of draping, namely how the orientation of the IMF in a plane perpendicular to the Sun-Earth line (the clock angle) is altered by draping in the magnetosheath close to the dayside magnetopause. The clock angle of the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 28 publications
6
37
1
Order By: Relevance
“…The larger differences between Wind and the other spacecraft observed after ∼19:00 UT are caused by incorrect time shifts of the data for those structures. Our data set fits well in the 70 % as found by Coleman (2005).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The larger differences between Wind and the other spacecraft observed after ∼19:00 UT are caused by incorrect time shifts of the data for those structures. Our data set fits well in the 70 % as found by Coleman (2005).…”
Section: Discussionsupporting
confidence: 84%
“…The draping of the IMF over the Earth's magnetosphere was studied by Coleman (2005) using Geotail and Interball-Tail data. This was done in order to study whether "perfect draping" (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMF is non-uniform, having structure on all spatial scales, and the draping process is far from that of a laminar flow approximation. It has long been recognised that the solar wind power spectrum is consistent with that of turbulence [Coleman, 2005;Goldstein and Roberts, 1999], with an inertial range extending from $1 minute to $100 hours. Other analyses show multifractal scaling of velocity and magnetic field from $1 minute to $100 minutes [Hnat et al, 2002[Hnat et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Other analyses show multifractal scaling of velocity and magnetic field from $1 minute to $100 minutes [Hnat et al, 2002[Hnat et al, , 2003. Coleman [2005] showed that the clock angle of the magnetosheath field near the magnetopause can differ from the (suitably time-delayed) IMF clock angle to a significant extent: this angular difference has a standard deviation of roughly 40deg, and the global distribution of clock angles is better characterised as ''perfect draping plus noise'' than by a hydrodynamic approximation.…”
Section: Introductionmentioning
confidence: 99%